-4(-2t+1)=-(-4+10t)

Simple and best practice solution for -4(-2t+1)=-(-4+10t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-2t+1)=-(-4+10t) equation:


Simplifying
-4(-2t + 1) = -1(-4 + 10t)

Reorder the terms:
-4(1 + -2t) = -1(-4 + 10t)
(1 * -4 + -2t * -4) = -1(-4 + 10t)
(-4 + 8t) = -1(-4 + 10t)
-4 + 8t = (-4 * -1 + 10t * -1)
-4 + 8t = (4 + -10t)

Solving
-4 + 8t = 4 + -10t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '10t' to each side of the equation.
-4 + 8t + 10t = 4 + -10t + 10t

Combine like terms: 8t + 10t = 18t
-4 + 18t = 4 + -10t + 10t

Combine like terms: -10t + 10t = 0
-4 + 18t = 4 + 0
-4 + 18t = 4

Add '4' to each side of the equation.
-4 + 4 + 18t = 4 + 4

Combine like terms: -4 + 4 = 0
0 + 18t = 4 + 4
18t = 4 + 4

Combine like terms: 4 + 4 = 8
18t = 8

Divide each side by '18'.
t = 0.4444444444

Simplifying
t = 0.4444444444

See similar equations:

| 4*x-9=20 | | h(0)=-16t^2(1)+95(1)+0 | | 9x/x+3-2x-21/x+3 | | -6=y/7 | | x^30=x | | h(0)=-16t^2(1)+28(1)+5 | | -3(x+5)=4(x-1) | | -2p-4(2p+9)=6p-10 | | y^2-16y+63=0 | | h(0)=-16t^2(t)+28(t)+5 | | -4x-6y=-28 | | h(0)=-16t^2(0)+28(0)+5 | | 4+2*x=7+x | | -x+7=-16 | | 2/5p=32.7 | | 25-3(6-x)=7 | | 5x+3=-(x-21) | | 8-x*2=20+x | | 4x-2=7x-4x | | 8-x^2=20+x | | s-4=5 | | 2/3-5/4=-1/5y+4/3y | | 2x+1=5x-4 | | 3+4(x-3)=-13 | | 1+-5x=7-6x | | 4x-8=-52 | | 3+4(x-3)=13 | | 7x=7/5 | | 0=-16t^2+36t+10 | | 6-wx=vx+3 | | 3x-8-1=x-3-4+2x | | 3-7x+5=-4/7x-3 |

Equations solver categories